Analysis of Internal Marketing Effect on Employee’s Job Satisfaction (Study in The Oberoi Hotel - Bali) - Dyah Ratri Satiti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Tight competition between companies with others makes marketing become one of tool that company needs to improve. Many successful companies are because they can implement the concept of marketing well. It is not only about how to sell the product to customer, but also make the customer itself become loyal and satisfy with product offered. Customer itself consists of two kinds, which are external and internal customer. Internal customers are the people in the company itself; it can be partner or employee. Implementation of internal marketing is the company trying to make their employees as their external customer. This study aims to investigate the influence of the relationship between internal marketing and job satisfaction of employees with independent variables that consist of training, motivation,empowerment, and communication. This study categorized in explanatory research, based on the fact that the purpose of this study was to clarify the relationship and influence of several variables that have been defined. This study examines employees of The Oberoi Hotel - Bali. A questionnaire used to collect data with 128 samples from employee in level R.L.5 to R.L.12 selected by probability sampling. The research instrument was tested by validity and normality test. To analyze the data, regression analysis method that including multicolinearity, heteroscesdasticity, and normality test are used. Results from this study are motivation and communication has a significant effect to employee job satisfaction. Keywords : marketing, internal customer, internal marketing, job satisfaction.